MARES: Navigation, Control and On-board Software - Aníbal Matos (2009)
MARES, or Modular Autonomous Robot for Environment Sampling, is a 1.5m long AUV, designed and built by the Ocean Systems Group. The vehicle can be programmed to follow predefined trajectories, while collecting relevant data with the onboard sensors. MARES can dive up to 100m deep, and unlike similar-sized systems, has vertical thrusters to allow for purely vertical motion in the water column. Forward velocity can be independently defined, from 0 to 2 m/s. Major application areas include pollution monitoring, scientific data collection, sonar mapping, underwater video or mine countermeasures.